1980 sonrası devlet politikalarının Türkiye’nin tarımsal dönüşümüne etkileri - Önal, Nevzat Evrim (My University, 2007)
THE EFFECTS OF STATE POLICIES ON TURKEY’S AGRICULTURAL TRANSFORMATION AFTER 1980 Since the foundation of Turkish Republic, agricultural sector have provided the means of subsistence to an important part of the population. It have also been a very important part of the economy and one of the main determinants of state policy and politics. Until 1980’s, a complex agricultural subsidization policy was designed and many institutions had been formed in line with this policy. The purpose of this system was to further the interests of the landowners on one hand and to keep in check the breaking away of the rural masses from agricultural production on the other. The state have gradually started to dismantle its protectionist and interventionist agricultural policy after 1980. This process picked up speed after 1998 and gained a substantial momentum after the financial crisis in 2001. As governmental body diminished and many state institution were privatized, agricultural policy was redesigned in line with these changes. The old system of agricultural subsidization was abolished and agricultural sector was opened to the effects of the natural course of capitalist development. The results of this was, and still is devastating to millions who make their living from agriculture. The transformations in the state’s agricultural policy after 1980, and the effects of this transformation on agricultural sector and peasantry is examined in this study.
Keywords: Ekonomik Gelişim_Tarım_Türkiye; Kırsal Bölgeler_Ekonomik Gelişim; Tarım Politikası_Türkiye